Variability and improvement of optical and antimicrobial performances for CQDs/mesoporous SiO2/Ag NPs composites via in situ synthesis - Cheng Youliang (De Gruyter, 2021)
To change the optical properties and improve the antibacterial performances of carbon quantum dots (CQDs) and Ag NPs, mesoporous SiO2 spheres were combined with them to form the composites. In this paper, CQDs with a uniform size of about 3.74 nm were synthesized using glucose as carbon source. Then, CQDs/mesoporous SiO2/Ag NPs composites were obtained in situ under UV light irradiating by using mesoporous SiO2 and Ag NO3 as the carrier and silver resource, respectively. The diameter of CQDs/mesoporous SiO2/Ag NPs particles was in the range of 200–250 nm. With the increase in irradiating time, the red-shift in the UV-Vis spectrum for as-prepared CQDs/mesoporous SiO2/Ag NPs composites was found, and the adsorption peak was widened. In addition, the composites showed a high antibacterial activity against Staphylococcus aureus and Escherichia coli via disc diffusion method. These results indicated that inhibition circles for Ag NPs/mesoporous SiO2/CQDs and mesoporous SiO2/Ag NPs were similar in diameter. Furthermore, the two composites had a better bactericidal performance compared with other particles. Therefore, as-prepared CQDs/mesoporous SiO2/Ag NPs composites in this paper have great potential applications for fluorescent materials and antibacterial materials.